Impact of co-exposure to Chaetoceros spp. and Tenacibaculum maritimum on Atlantic salmon (Salmo salar) gills - E. Fajei; S.K. Whyte; M. Soto-Davila; K. Eslamloo; L. Groves; K. Storey; R. Ghanei-Motlagh; D.B. Groman; S.L. Purcell; M.D. Fast (Aquaculture, 2026)

Associations between individual-level social capital, homophilous and heterophilous social network diversities, and climate stewardship in Japan - Ayako Morita; Nobutoshi Nawa; Douglas Storey; Carol R. Underwood; Pamela J. Surkan; Takeo Fujiwara (Journal of Environmental Management, 2025)

Detailed hydrocarbon speciation and particulate matter emissions during cold-start from turbocharged and naturally aspirated trucks - Melanie Moses-DeBusk; John M.E. Storey; Samuel A. Lewis Sr.; R. Maggie Connatser; Shannon M. Mahurin; Shean Huff; Cyril V. Thompson; Yensil Park (Fuel, 2023)

Mineral-whole rock isotope fidelity? A comparative study of Hf-Nd-O from high Ba-Sr granitoids - E. Bruand; C. Storey; M. Fowler; B. Dhuime; R. Doucelance (Chemical Geology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Utility and optimization of LANDSAT-derived burned area maps for southern California - Emanuel Arnal Storey; Krista R. Lee West; Douglas A. Stow (International Journal of Remote Sensing, 2021)

Short-term neuromuscular, morphological, and architectural responses to eccentric quasi-isometric muscle actions - Dustin J. Oranchuk; André R. Nelson; Adam G. Storey; Shelley N. Diewald; John B. Cronin (European Journal of Applied Physiology, 2021)

Extended liquid chromatography high resolution mass spectrometry screening method for veterinary drug, pesticide and human pharmaceutical residues in aquaculture fish - Sherri B. Turnipseed; Joseph M. Storey; I-Lin Wu; Wendy C. Andersen; Mark R. Madson (Food Additives & Contaminants: Part A, 2019)

Impacts of Air-Fuel Stratification in ACI Combustion on Particulate Matter and Gaseous Emissions - Melanie Moses-DeBusk; Scott J. Curran; Samuel A. Lewis; R. Maggie Connatser; John M. E. Storey (Emission Control Science and Technology, 2019)

Purification of carbamoyl phosphate synthetase 1 (CPS1) from wood frog (Rana sylvatica) liver and its regulation in response to ice-nucleation and subsequent whole-body freezing - Stuart R. Green; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2019)

U–Pb isotopic dating of titanite microstructures: potential implications for the chronology and identification of large impact structures - K. Papapavlou; J. R. Darling; D. E. Moser; I. R. Barker; L. F. White; P. C. Lightfoot; C. D. Storey; J. Dunlop (Contributions to Mineralogy and Petrology, 2018)

Biomimetic Dissolution: A Tool to Predict Amorphous Solid Dispersion Performance - Michael M. Puppolo; Justin R. Hughey; Traciann Dillon; David Storey; Susan Jansen-Varnum (AAPS PharmSciTech, 2017)

Acute effects of heated resistance exercise in female and male power athletes - Julia R. Casadio; Adam G. Storey; Fabrice Merien; Andrew E. Kilding; James D. Cotter; Paul B. Laursen (European Journal of Applied Physiology, 2017)

Community‐based monitoring of New Zealand stream macroinvertebrates: agreement between volunteer and professional assessments and performance of volunteer indices - R. G. Storey; A. Wright‐Stow (New Zealand Journal of Marine and Freshwater Research, 2017)
Community‐based monitoring of freshwaters (a form of citizen science) is an area of growing interest globally. It could be used to augment professional monitoring in New Zealand, as is done in other countries, if the agreement between volunteer and professional assessments is close enough. We compared volunteer benthic macroinvertebrate data with professional data from parallel monitoring over 18 months at 8 sites across New Zealand. We found strong correlations ( r =0.77–0.85) and little bias between volunteer data using volunteer indices and professional data using a professional index. Volunteer classifications in stream ‘quality classes' agreed with professional classifications in 70–85% of cases. Two volunteer‐level biotic indices showed slightly different correlation and bias with respect to the professional biotic index. A modified volunteer index could blend the strengths of each. Presence‐absence indices correlated as well as, or better than, their quantitative versions. We conclude that, given suitable training and support, volunteer assessments of stream ecological condition agree well with, and are only slightly more variable than, professional assessments.

Oviposition site selectivity of some New Zealand aquatic macroinvertebrate taxa and implications for stream restoration - R. G. Storey; D. R. Reid; B. J. Smith (New Zealand Journal of Marine and Freshwater Research, 2017)
In many stream restoration projects, macroinvertebrates characteristic of natural conditions do not return despite habitat improvements. One contributing factor may be lack of oviposition sites for some taxa. To understand oviposition requirements of five taxa, we investigated their egg mass distributions on rocks in streams in the Waikato region, New Zealand. We compared insect taxa with aerial adults (caddisfly families Hydrobiosidae and Hydropsychidae, and blackfly species Austrosimulium australense and Austrosimulium sp.) to the fully aquatic limpet Latia neritoides . Egg masses of all taxa were highly aggregated, indicating strong site selection. Hydrobiosidae and both Austrosimulium species preferred ovipositing on emergent rather than submerged rocks. When ovipositing on submerged rocks, Hydropsychidae, Hydrobiosidae and A. australense preferred rocks Latia preferred large rocks (as did all taxa except Austrosimulium sp.) in reaches with low riparian shade. To allow recolonisation and/or persistence of these taxa, restored stream reaches need at least some rocks (or other features) with these characteristics.

Rheomorphic ignimbrites of the Rogerson Formation, central Snake River plain, USA: record of mid-Miocene rhyolitic explosive eruptions and associated crustal subsidence along the Yellowstone hotspot track - Thomas R. Knott; Marc K. Reichow; Michael J. Branney; David R. Finn; Robert S. Coe; Michael Storey; Bill Bonnichsen (Bulletin of Volcanology, 2016)

Analysis of lasalocid residues in grease and fat using liquid chromatography-mass spectrometry - Susan B. Clark; Joseph M. Storey; Justin R. Carr; Mark Madson (Food Additives & Contaminants: Part A, 2015)

Site-specific water quality guidelines: 1. Derivation approaches based on physicochemical, ecotoxicological and ecological data - R. A. van Dam; C. L. Humphrey; A. J. Harford; A. Sinclair; D. R. Jones; S. Davies; A. W. Storey (Environmental Science and Pollution Research, 2014)

QTL involved in the modification of cyanidin compounds in black and red raspberry fruit - J. M. Bushakra; C. Krieger; D. Deng; M. J. Stephens; A. C. Allan; R. Storey; V. V. Symonds; D. Stevenson; T. McGhie; D. Chagné; E. J. Buck; S. E. Gardiner (Theoretical and Applied Genetics, 2013)

Genetic structure of Melanotaenia australis at local and regional scales in the east Kimberley, Western Australia - R. D. Phillips; A. W. Storey; M. S. Johnson (Journal of Fish Biology, 2009)
The Kimberley region of Western Australia possesses a poorly studied freshwater fish fauna with high endemism in an aquatic landscape subject to monsoonal floods and dry season isolation. In the first population genetic study of freshwater fish in this region, the authors tested the effects of geographic barriers on genetic structure at multiple spatial scales in east Kimberley populations of the western rainbowfish, Melanotaenia australis , the most widespread and abundant species in the region. Based on allozyme comparisons, hierarchical analysis of F ST revealed increasing genetic subdivision with spatial scale. Minimal genetic structure within creeklines demonstrated that wet season dispersal, rather than dry season isolation, determines genetic structure at small scales. At the scale of sub‐catchments, a pattern of isolation by distance along creeklines was evident. Genetic subdivision between adjacent river systems was greater between rivers separated by a plateau than by lowlands. This implies greater connectivity of populations in lowland areas and may explain the greater similarity of the east Kimberly freshwater fish fauna with lowlands to the east than with the more rugged regions to the west. Similarly, greater connectivity between lowland populations may account for the on‐average larger distribution of lowland Melanotaeniids.

The Canon of Potato Science - P. C. Struik; W. J. M. Lommen; A. J. Haverkort; R. M. J. Storey (Potato Research, 2007)

The Canon of Potato Science: 44. Damage and Bruising - R. M. J. Storey (Potato Research, 2007)

Cold-loving microbes, plants, and animals—fundamental and applied aspects - R. Margesin; G. Neuner; K. B. Storey (The Science of Nature, 2007)

Characterization of ‘Schizokinen’; a dihydroxamate-type siderophore produced by Rhizobium leguminosarum IARI 917 - E. P. Storey; R. Boghozian; James L. Little; Douglas W. Lowman; R. Chakraborty (BioMetals, 2006)

Influence of type of cancer and hematopoietic stem cell transplantation on clinical presentation of Pneumocystis jiroveci pneumonia in cancer patients - H. A. Torres; R. F. Chemaly; R. Storey; E. A. Aguilera; G. M. Nogueras; A. Safdar; K. V. I. Rolston; I. I. Raad; D. P. Kontoyiannis (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

The roles of proteolysis and nuclear localisation in the toxicity of the polyglutamine diseases. A review - R. Walsh; E. Storey; D. Stefani; L. Kelly; V. Turnbull (Neurotoxicity Research, 2005)

Diffusion tensor imaging of subcortical brain injury in patients infected with human immunodeficiency virus - Ann B Ragin; Ying Wu; Pippa Storey; Bruce A Cohen; Robert R Edelman; Leon G Epstein (Journal of NeuroVirology, 2005)

UV-B irradiation stimulates the promoter activity of the high-risk, cutaneous human papillomavirus 5 and 8 in primary keratinocytes - B. Akgl; W. Lemme; R. Garca-Escudero; A. Storey; H. J. Pfister (Archives of Virology, 2005)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Recovery of three New Zealand rural streams as they pass through native forest remnants - Richard G. Storey; Don R. Cowley (Hydrobiologia, 1997)

Suppression of reproductive development and longevity in the redshouldered leaf beetle,Monolepta australis (Col.: Chrysomelidae) by the tachinid,Monoleptophaga caldwelli (Dipt.) - H. A. C. Fay; R. I. Storey; S. G. Defaveri; J. D. Brown (BioControl, 1993)